Short- and long-term effects of transfers on football clubs’ sport performance - Wanat, Tomasz; Leksowski, Łukasz (Journal of Education, Health and Sport, 2022)
One of the important elements of football club quality management is the sale and purchase of player’s cards. These activities have important implications for the financial and sport performance of football clubs. The purpose of this paper is to determine how players transfers affect football teams’ sport performance. Data on transfers and sport performance came from available databases. They covered the period from 2004/05 to 2018/19 (before the pandemic). For data analysis, a series of hierarchical analysis of regression were conducted. The results show that there is an effect of transfers on football teams’ sport performance but it explains a relatively small amount of football club’s sport performance. The impact from a transfer in a given year affects sport performance not only in the same year, but also in subsequent years. However, the effect of transfer disappears when control variables are introduced. Thus, the general conclusion from the study is that there is no overall effect of transfers on teams’ sport performance. The analyses were conducted only on clubs from the 5 major European leagues and football clubs that were continuously present in the top division. Due to the fact that it included mainly the strongest clubs, the results are relevant for clubs wishing to build up their sporting position on the European market. It is less relevant for weaker clubs. The study consisted of using data over a period of several years, which provides an opportunity to trace the dynamics of change and long-term effects, which is rarely analyzed in the sports literature.